Measures of Criminal Law to Counteract Juvenile Alcoholism - Yu. S. Pestereva; Ye. I. Chekmezova (Сибирское юридическое обозрение, 2015)
The article dwells on the effectiveness of measures of criminal law aimed to reduce distribution of alcohol among juveniles. The author analyses judicial practice of inflicting punishment according to the article 151.1 of the Criminal Code of the Russian Federation.